Introducing the Canadian Thoracic Society Framework for Guideline Dissemination and Implementation, with Concurrent Evaluation - Samir Gupta; Christopher Licskai; Anne Van Dam; Louis-Philippe Boulet (Canadian Respiratory Journal)
The Canadian Thoracic Society (CTS) is leveraging its strengths in guideline production to enable respiratory guideline implementation in Canada. The authors describe the new CTS Framework for Guideline Dissemination and Implementation, with Concurrent Evaluation, which has three spheres of action: guideline production, implementation infrastructure and knowledge translation (KT) methodological support. The Canadian Institutes of Health Research ‘Knowledge-to-Action’ process was adopted as the model of choice for conceptualizing KT interventions. Within the framework, new evidence for formatting guideline recommendations to enhance the intrinsic implementability of future guidelines were applied. Clinical assemblies will consider implementability early in the guideline production cycle when selecting clinical questions, and new practice guidelines will include a section dedicated to KT. The framework describes the development of a web-based repository and communication forum to inventory existing KT resources and to facilitate collaboration and communication among implementation stakeholders through an online discussion board. A national forum for presentation and peer-review of proposed KT projects is described. The framework outlines expert methodological support for KT planning, development and evaluation including a practical guide for implementers and a novel ‘Clinical Assembly – KT Action Team’, and in-kind logistical support and assistance in securing peer-reviewed funding.